KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMK YASMIDA AMBARAWA KABUPATEN PRINGSEWU - Ngarifin, Syeh Al; Muhtarom, Muhtarom; Umurohmi, Ulfah (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2017)
This study aims to determine how the headmaster of the SMK Yasmida Ambarawa foster and control the employee for the advancement of teachers and the school, including the pedagogical side and the professionalism of the teacher-led. SMK Yasmida Ambarawa is a private school in sub urban region with the varied of human resource and entry 8 major categories of school-based pilot vocational national level. This is a challenge and a great effort for a headmaster with the reality high enthusiasts to reach thousands students, is a good managerial proof applied by headmaster. This is the one interesting researcher for reviewing more about skills in vocational headmaster of SMK Yasmida Ambarawa.Headmaster of SMK Yasmida Ambarawa have done menagerial through of process; a) preparation of work plan of the school, either half or annual, preparing curriculum simultaneously divide tasks to all teachers and employees along with the letter of assignment and schedule. b) leads the coordination and meeting, providing quick and direct information, conduct periodic guidance for teachers and employees. C) improve the welfare of teachers with loads attention honorarium based tasks, perform evaluations comprehensive and rewards for teachers its achievement.